The visceral remains: revealing the human desire for performance through personal narratives of Alzheimer's Disease*. Issue 2 (3rd April 2019) - Scott, Julie-Ann
ABSTRACT: Through analyzing the narratives of two elders experiencing Alzheimer's Disease (AD) as personal performances of identity, this essay explores repetition in interpersonal interactions beyond a familiar diagnostic sign of the progression of memory loss. The author argues that, as AD hinders the body's ability to diversify language and adhere to cultural expectations for personal performances, the visceral desire that compels humans to perform for/with one another surfaces in concentrated vivid form: bodies responding to the world desire to reiterate meanings that matter to others, knowing these meanings are only real to the extent they are (re)performed in daily life.